Secondary Syphilis, Anal Condylomata Acuminata, and HIV in Bisexual Male Patient: Another Point of View, Time Evaluation Based on CD4 and Management - Vina Ajeng Puspa Dewi; Satiti Retno Pudjiati (Faculty of Medicine, Universitas Airlangga, 2015)
Background: A meta analysis study in China states that male bisexual has higher incidence rate for HIV and syphilis than male-sex-male. Syphilis eases the transmission of HIV, vice versa HIV breaches the integrity of mucosal epithelial barrier, allowing translocation virus and bacterial. Syphilis has higher incidence rates in HIV-infected compare with HIV-uninfected patients. Syphilis influences CD4 of patient. We try discussing a case of secondary syphilis in male bisexual HIV in another point of view, to find which one earlier based on CD4 count. Purpose: to understand another point of view, time evaluation based on CD4 and management in secondary syphilis, anal condyloma accuminata, and HIV in bisexual male patient Case: A 19 years old male bisexual patient complained erythematous rash all over his body, no itch or pain; TPHA 1/2560, VDRL 1/128, positive HIV 3antibody, and CD4 425cell/mm. Case management: HIV onset, considering decrease of CD4 in syphilis or not, are 2-5,8years and 3,08-7,7years, respectively. Therapy was given as single dose benzatin penisilin 2,4billion IU intramuscular. Conclusion:HIV infection occurred before syphilis. No differences in management with HIV-uninfected syphilis patient, more often evaluation interval needed.Key words: syphilis, HIV, bisexual, CD4, onset, management.